Peru Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2017)
Peru has been one of the most prominent performers in Latin America in the last 25 years. Peru is characterized by a complex and diverse geography that holds wealth in natural resources and several spatial development challenges.Peru has a remarkable cultural heritage and rich ethnic diversity. Peru’s geography, natural endowments, and diverse population have shaped its unbalanced economic development.Geography and resource abundance have thus led to a spatial concentration of economic activities and opportunities, creating large disparities in development across the country’s territory and its population groups.The virtuous cycle of growth and shared prosperity can be explained in large part by a combination of two main forces: favorable exogenous conditions and successful macro structural reforms.The new headwinds indicate that the past virtuous cycle of growth and shared prosperity may have reached its limit.These new headwinds highlight two structural challenges that have emerged from Peru’s specific endowments, and that constrain the opportunities for income growth of the bottom 40 percent. First, the persistence of large spatial disparities in development consistently undermine the ability of certain population groups, particularly indigenous and Afro Peruvians, from overcoming poverty. Moreover, the capital-centric development model contributes to imbalances within the urban sector.Peru’s second structural challenge relates to the large productivity gap of its private sector relative to its peers, which is constraining the demand for better-paying jobs and income opportunities. Peru’s low aggregate productivity stems in part from substantial misallocation of capital and labor as its more productive firms do not necessarily hire more workers or invest more.The Systemic Country Diagnostic (SCD) prioritizes policy constraints that have the greatest impact on Peru’s structural challenges of reducing the large spatial disparities and boosting private sector productivity. The SCD uses the following selection criteria to identify the constraints with the largest impact on achieving shared prosperity going forward. First, it identifies constraints that significantly affect one or both of the two main structural challenges. Second, it identifies policy constraints that present synergies to overcome these structural challenges. Third, it identifies constraints that support the sustainability of addressing Peru’s structural challenges. Applying the three criteria described above, the SCD identifies a set of constraints that are pivotal to address Peru’s two main structural challenges and should thus be the focus of policies in coming years.